1990
DOI: 10.1002/ptr.2650040209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Echinacea purpurea extracts on fibroblast populated collagen lattice contraction

Abstract: The fibroblast populated collagen lattice was used to study the influence of extracts from roots or herbal parts of Echinacea purpurea on the collagen contracting abTty of C3H10n/2 mouse fibroblasts. Collagen gel contraction was inhibited by herb and root extracts which were added at the time of preparation of the gel. Inhibition was dependent on the amount of extract, the initial cell density and the collagen concentration used for preparation of the gel. When cell density was increased or collagen concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…[ 35 ] Also, it is reported that the ethanol extracts of both aerial parts and roots of the plant have inhibited fibroblast-induced collagen concentration. [ 36 ] The effects of Echinacea and some of its compounds on NF-κB expression by Jurkat cells (a human T-cell line) were assessed in the presence and absence of stimulation by LPS and phorbol 12-myristate 13-acetate (PMA). NF-κB is a nuclear transcription factor stimulating the expression of some genes such as key factors of inflammation, e.g., TNF-α, IL-1, chemokines, adhesion molecules, and COX-2.…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…[ 35 ] Also, it is reported that the ethanol extracts of both aerial parts and roots of the plant have inhibited fibroblast-induced collagen concentration. [ 36 ] The effects of Echinacea and some of its compounds on NF-κB expression by Jurkat cells (a human T-cell line) were assessed in the presence and absence of stimulation by LPS and phorbol 12-myristate 13-acetate (PMA). NF-κB is a nuclear transcription factor stimulating the expression of some genes such as key factors of inflammation, e.g., TNF-α, IL-1, chemokines, adhesion molecules, and COX-2.…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…The ethanolic extract of aerial plant parts and roots of the Echinacea purpurea strongly reduced the concentration of collagen proteins that is induced by fibroblast cells. 57 The extract of dried root of E. purpurea given to mice, effectually retarded the Carrageenan-promoted paw edema 58 and this response may be associated with the suppression of COX-1 and COX-2 by the functioning of alkamides. 59…”
Section: Anti-inflamatory Effectsmentioning
confidence: 99%
“…대표적인 플라보노이드인 quercetin 과 kaempferol이 HaCaT세포의 hyaluronic acid 생성을 촉진한다 고 보고되었으며 (Kim et al, 2005), 그 중 quercetin은 같은 속인 Echinacea purpurea에 포함되어 있다 (Coelho et al, 2020). Echinacea 추출물은 과거부터 플라보노이드 및 폴리페놀에 성 분에 의해 피부의 광노화를 막는다고 알려져 있으며 (Facino et al, 1995), 콜라겐 합성을 촉진시켜 상처 치료 속도를 증가시킨다고 알 려져 있다 (Zoutewelle & van Wijk, 1990).…”
unclassified